Ethics and management - Mihai, Teodorescu (Marketing & Menedzsment, 2019)
Ethical problems represent real managerial dilemmas because they represent conflicts between the economic performances of a firm and its social performances. The interest for an ethical behaviour is not so new, but only now there are intense concerns for moral actions for maintaining competition and public trust in the developed activities.